Revision Total Knee Arthroplasty (Springer International Publishing, 2018)
Now in its fully revised and updated second edition, this comprehensive, how-to text covers all aspects of revision total knee arthroplasty (TKA), complete with step-by-step descriptions of surgical techniques. Divided thematically into three main sections, part I discusses evaluation and diagnosis of the failed TKA, including imaging and updates on incidence and rationale for reoperation. General principles of revision surgery are presented in part II, addressing skin and extensile exposure, component removal, allografts, metaphyseal sleeves and cones, femoral and tibial alignment, and restoration of stability. Part III presents the many special considerations that come into play with revision TKA, including periprosthetic fracture, infection, stiffness and other post-operative complications and complexities. The role of arthrodesis and the economics of revision TKA are also elucidated. Utilizing the most current evidence and generously illustrated, orthopedic surgeon s, sports medicine specialists and residents alike will find Revision Total Knee Arthroplasty, Second Edition a thorough and informative resource when treating the patient following knee replacement surgery.